First record of Scelidotheriinae Ameghino (Xenarthra, Mylodontidae) from the Chasicoan Stage/Age (late Miocene) of Argentina - Miño Boilini, Ángel Ramón (2014)
The subfamily Scelidotheriinae constitutes a group of mylodontids widely represented in the Quaternary of South America; however, the fossil record of the Neogene taxa is still scarce. In the present paper, a new specimen of this subfamily, corresponding to a right partial hemimandible with complete dental series, is reported. The material was recovered from the lower levels of the Arenisca Albardón Member of the Loma de Las Tapias Formation (San Juan Province, Argentina), assigned to the late Miocene. This finding represents the first record of a member of the Scelidotheriinae from the Chasicoan Stage/Age and provides new information about the anatomical characteristics and the geographic distribution of the Neogene representatives of this subfamily.